Evaluation of Internal Receivables Control at PT Merak Jaya - Dini Ayu Pramitasari; Rusdiyanto Rusdiyanto; Bustanul Ulum; Anisaul Hasanah; Mochammad Syafii (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to review the receivables control and the management policy of unbilled receivables and the receivables management policy applied to precast concrete iron distributor companies. This research provides insight into best practices in receivables management. The method used is descriptive with a qualitative approach, where the selection of informants is carried out based on their knowledge related to relevant information in the context of the research. The main informant consists of financial staff who have direct experience in receivables control. The findings of the study show that the company has implemented quite good receivables control, as seen from the existence of systematic billing procedures to clients. However, the company does not have an adequate receivables management policy, the absence of clear credit standards and credit requirements are the main obstacles in minimizing the risk of non-collectible receivables. The implications of these findings emphasize the need for companies to formulate more comprehensive accounts receivable management policies to improve the efficiency and effectiveness of the collection process and reduce potential financial losses. The originality of this research lies in its focus on the precast concrete iron distribution sector in Indonesia, as well as an in-depth analysis of the specific challenges in receivables control practices in the construction sector.